NURSING STUDENTS’ MOTIVATION TOWARD BLENDED LEARNING AT A PRIVATE UNIVERSITY IN TANGERANG - Daniel Yunihardi Pratama; Lifia Sopacua; Otniel Natanael Sinambela; Yakobus Siswadi; Lani Natalia Watania (Nursing Current: Jurnal Keperawatan, 2022)
Motivation can be a driving force for learning that is manifested by the attention of students in blended learning. Blended learning is a combination of online learning and face-to-face learning models.  Faculty of Nursing at one private university in Tangerang, is currently developing a blended learning model. The learning is applied to several subjects including Emergency and Critical Care and Disaster Management courses. When the pandemic hit Indonesia, the education system suddenly shifted to online learning. It then pushed students and teachers to master the use of technology, in order to ensure the effectiveness of its implementation. It is indeed significant, given that there are several challenges with a blended learning model, such as internet connection, inadequate facilities or devices, and students’ tendency to procrastinate. It is also important to know students’ perception toward blended learning for the better implementation in the future. This study sought  to explore the motivation of nursing students at one private university in Tangerang toward blended learning. To achieve the objective, a descriptive quantitative research method was utilized. The sample consisted of 207 third year nursing students who learned with a blended learning method. The data were collected using The Motivated Strategies for Learning Questionnaire (MSLQ) in May 2020 by online survey form. The data were then analyzed using univariate analysis. It showed that 70% students had high learning motivation while the remaining 30% had  low learning motivation.  Hence, blended learning was assumed to be effective and worth keeping for nursing education.